Effects of kaolin and limestone on infestation of South American fruit fly in citrus orchards. Issue 1 (2nd January 2019) - Ourique, Cláudia Bernardes; Redaelli, Luiza Rodrigues; Efrom, Caio Fábio Stoffel; Pedrini, Douglas
ABSTRACT: This study evaluated the effects of applying mineral films on infestations by Anastrepha fraterculus (Wied.) (Dip.: Tephritidae) in Céu and Valencia sweet oranges ( Citrus sinensis ). The treatments consisted of either kaolin or liquid limestone (calcium carbonate) at 20% concentrations, both with addition of 0.1% Break Thru® adhesive spreader, plus a control treatment (no applications). The spraying was performed in the Céu orchard in Pareci Novo, state of Rio Grande do Sul (RS), Brazil, from March to April 2015, and in the Valencia orchard in Taquari, RS, from May to August 2015. Each tree received 1.5 L of the respective formulations, applied by spraying. Fruits from the canopy and from the ground under each tree were harvested and arranged in containers with sand and stored in a chamber or a greenhouse for 30 days. The sand was then sieved and the fruits opened to remove the larvae and/or pupae. The physical-chemical attributes of the fruits harvested at the last sampling (during fruit harvest) were analysed. In both orchards, fruits collected from the canopy had similar numbers of pupae + larvae per canopy for kaolin and calcium carbonate treatments, and both were lower than in the control treatment. The fruits showed no physiological changes resulting from the treatments.